2020
DOI: 10.1002/mds.28304
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structural Changes in Focal Dystonia—What About Task Specificity? A Multimodal MRI Study

Abstract: Background The neural basis of task specificity in dystonia is still poorly understood. This study investigated gray and white matter (WM) brain alterations in patients with task‐specific dystonia (TSD) and non‐task‐specific dystonia (NTSD). Methods Thirty‐six patients with TSD (spasmodic dysphonia, writer's cramp), 61 patients with NTSD (blepharospasm, cervical dystonia), and 83 healthy controls underwent 3D T1‐weighted and diffusion tensor magnetic resonance imaging (MRI). Whole brain cortical thickness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 58 publications
3
34
0
Order By: Relevance
“…retrospectively analysed 1,215 normal elderly individuals and found that albuminuria was associated with brain cortical thinning, whereas frontal and occipital regions were the most related regions, implying that albuminuria may directly cause neuronal toxicity and eventually result in TH alterations [38] . Alterations of TH have also been reported in dystonia, voice tremor, Parkinson's disease, depression, schizophrenia, attention deficit hyperactivity disorder, and insomnia [39] , [40] , [41] , [42] . Our estimates indicate that albuminuria causally reduces global TH.…”
Section: Discussionmentioning
confidence: 94%
“…retrospectively analysed 1,215 normal elderly individuals and found that albuminuria was associated with brain cortical thinning, whereas frontal and occipital regions were the most related regions, implying that albuminuria may directly cause neuronal toxicity and eventually result in TH alterations [38] . Alterations of TH have also been reported in dystonia, voice tremor, Parkinson's disease, depression, schizophrenia, attention deficit hyperactivity disorder, and insomnia [39] , [40] , [41] , [42] . Our estimates indicate that albuminuria causally reduces global TH.…”
Section: Discussionmentioning
confidence: 94%
“…The interplay between basal ganglia and cerebellum highlights that the cerebellum is a potential treatment target for dystonia (Tewari et al 2017). An unmet need in dystonia research is the uncertainty whether these new concepts apply to all or only a subgroup of dystonias (Tomic et al 2020). Other poorly understood aspects are the insufficient mapping of non-motor signs and the changes in non-motor-related circuits due to dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism behind the psychiatric features may relate to changes within a network involving the amygdala. Recently, by voxel based morphometry, patients with task specific dystonias showed enlarged amygdala volumes 16 . The amygdala is crucial in emotional regulation and alterations in amygdala volume has been linked with major depressive disorder 17 .…”
Section: Discussionmentioning
confidence: 99%